Modeling of continuous fermentation with nonlinear growth rate - J. L. Gordeeva; J. A. Ivashkin; L. S. Gordeev (Тонкие химические технологии, 2011)
The performance of a continuous bioreactor was theoretically analyzed for steady-state operation. The effect of substrate feed concentration and dilution rate was analyzed. Equations for estimation of productivity and of concentrations of the substrate and biomass were obtained.